Posttraumatic Growth and its correlates among survivors of adolescent and young adult cancer: A brief report - Barrett-Bernstein, Meagan; Wurz, Amanda; Brunet, Jennifer (Université d'Ottawa | University of Ottawa, 2019)
Objectives: The objectives of this study were to describe posttraumatic growth (PTG) levels among survivors of adolescent and young adult cancer (AYAs), and estimate relationships between PTG and medical (cancer type, age at diagnosis, time since treatment), behavioral (physical activity), and psychological (appearance evaluations, body satisfaction) variables. Methods: Eighty-eight AYAs (Mage=33 ± 4.4 years) completed a survey online that included the PTG-Inventory (PTG-I). Data were analyzed using descriptive statistics and bivariate correlations. Findings: Total and subdimension PTG-I scores indicated moderate-to-high PTG levels, with the highest and lowest scores reported for appreciation of life and spiritual change, respectively. Appearance evaluations was moderately and positively correlated with the spiritual change subdimension (r = .31, p < .001). Relationships between PTG and other variables were of weak magnitude and not statistically significant (rs = 0–.21, ps > .05). Conclusions: More research exploring variables related to PTG among AYAs is needed to better understand antecedents and outcomes of PTG.
This is an Accepted Manuscript of an article published by Taylor & Francis in Journal of Psychosocial Oncology on 2019 Oct 10, available at: https://doi.org/10.1080/07347332.2019.1664702.
Keywords: Adolescents and young adults; Oncology; Positive psychological changes; Quantitative study; Survivorship